Thermally-drawn fibers with spatially-selective porous domains - Benjamin Grena (Nature Portfolio, 2017)
Porous polymer fibers show great potential for a range of applications, but their simple structures typically limit their functionality. Here, the authors combine a thermal drawing process with polymer solution phase separation to fabricate porous multimaterial fibers with complex internal architectures.